The divergent effects of astrocyte ceruloplasmin on learning and memory function in young and old mice - Zhong-Da Li; Haiyan Li; Shaomeng Kang; Yan-Ge Cui; Huiwen Zheng; Peina Wang; Kang Han; Peng Yu; Yan-Zhong Chang (Cell Death and Disease, 2022)
Abstract Ceruloplasmin (CP) plays an important role in maintaining iron homeostasis. Cp gene knockout (Cp -/- ) mice develop a neurodegenerative disease with aging and show iron accumulation in the brain. However, iron deficiency has also been observed in 3 M Cp -/- mice. The use of systemic Cp gene knockout is insufficient to reveal specific functions for CP in the central nervous system. Considering recent discoveries that astrocytes synthetize the majority of brain CP, we generated astrocyte conditional Cp knockout (Cp Gfap cKO) mice, and found that iron contents decreased in the cerebral cortex and hippocampus of young (6 M) and old (18 M) Cp Gfap cKO mice. Further experiments revealed that 6 M Cp Gfap cKO mice exhibited impaired learning and memory function, while 18 M Cp Gfap cKO mice exhibited improved learning and memory function. Our study demonstrates that astrocytic Cp deletion blocks brain iron influx through the blood-brain-barrier, with concomitantly increased iron levels in brain microvascular endothelial cells, resulting in brain iron deficiency and down-regulation of ferritin levels in neurons, astrocytes, microglia and oligodendrocytes. At the young age, the synapse density, synapse-related protein levels, 5-hydroxytryptamine and norepinephrine, hippocampal neurogenesis and myelin formation were all decreased in Cp Gfap cKO mice. These changes affected learning and memory impairment in young Cp Gfap cKO mice. In old Cp Gfap cKO mice, iron accumulation with aging was attenuated, and was accompanied by the alleviation of the ROS-MAPK-apoptosis pathway, Tau phosphorylation and β-amyloid aggregation, thus delaying age-related memory decline. Overall, our results demonstrate that astrocytic Cp deletion has divergent effects on learning and memory function via different regulatory mechanisms induced by decreased iron contents in the brain of mice, which may present strategies for the prevention and treatment of dementia.